FATIGUE FAILURE OF NICKEL-TITANIUM INSTRUMENTS IN ENDODONTICS AND ITS INFLUENCING FACTORS - A Jusku; T Dodeková; J Staněk; B Özel; P Jirásek; V Polanská; Ľ Harvan (Czech Dental Chamber, 2022)
Introduction and aim: The fracture of Ni-Ti instruments is a complication that most dentists will sooner or later encounter in the dental office. There are mainly two basic mechanisms behind it and these are exceeding the cyclic fatigue limit, exceeding the torsional fatigue limit and their mutual combination. The purpose of this article is to describe the fracture mechanism of a nickel-titanium endodontic instrument based on cyclic fatigue, the influencing factors and related issues of laboratory testing. Methods: Literature searches were performed using PubMed (MEDLINE), ScienceDirect and the Wiley Online Library database. Keywords related to the topic were used to search the literature. Then suitable sources were selected. Instrument fracture mechanism: A cyclic fatigue fracture consists of three basic phases. Initiation, which is the period of time when morphological changes occur, especially on the surface and subsurface of the instrument, until the formation of the primary crack. After that the crack gradually grows with the formation of characteristic striations. As soon as the fracture toughness limit is exceeded, it is time for final failure and separation of part of the instrument. Factors affecting fracture: One of the most significant effects on fracture formation has the quality of the alloy. Today, rotary endodontic instruments can be divided according to their structure into the instruments with a predominance of martensite or austenite. From the point of view of cyclic fatigue, martensitic instruments are significantly more durable than austenitic. From a physical point of view, surface roughness has a direct effect on fracture formation as surface irregularities serve as predisposing points for stress concentration. The shape of the instrument also has an important effect, as the smaller diameter of the instrument and its core has a positive effect on the resistance to cyclic fatigue. As the cross-section area of the instrument increases, the tensile strain on its surface increases, thus, a faster failure occurs. The ambient temperature significantly affects the properties of the instruments. Higher temperature reduces resistance to cyclic fatigue. It should be kept in mind that the instrument may behave diametrically differently at room temperature compared to the root canal temperature. We must also not forget the parameters of the root canal, which fundamentally affect the failure of the instrument. The type of instrument movement kinematics in the root canal is also very important. From this point of view, we can clearly say that the rotational mode reduces the instruments's resistence to cyclic fatigue compared to reciprocal ones. An ideal irrigant has not yet been identified for cyclic fatigue testing. Conclusion: The topic of failure of endodontic instruments based on cyclic fatigue is very extensive. Its development and understanding can help the production of more durable instruments and thus minimize the presence of this complication in a general dental office.